2017
DOI: 10.1002/da.22659
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and neurobiological effects of aerobic exercise in dental phobia: A randomized controlled trial

Abstract: Our study provides evidence for an effect of moderate-intense exercise on clinical symptoms and sC in patients with dental phobia. Therefore, acute aerobic exercise might be a simple and low-cost intervention to reduce disorder-specific phobic fear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…Lidenberger et al reported in their study that taking physical exercise prior to dental treatment significantly reduces dental fear. The results of these studies are in concordance with our study (34). Unfortunately, in our country, studies of largescale regarding levels of physical activity are insufficient.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Lidenberger et al reported in their study that taking physical exercise prior to dental treatment significantly reduces dental fear. The results of these studies are in concordance with our study (34). Unfortunately, in our country, studies of largescale regarding levels of physical activity are insufficient.…”
Section: Discussionsupporting
confidence: 91%
“…Our country was included in a worldwide research related with child and adolescent health, held by the World Health Organization. In the 2009-2010 report of this study they stated that 19% of the girls and 27% of the boys at 11 years of age, 12% of the girls and 23% of the boys at 13 years of age, 9% of the girls and 18% of the boys at 15 years of age had at least 1 hour of medium and heavy levels of physical activity every day (34). 1871 high school students of adolescent age group from various ethnic groups participated in another study in the U.S., at the end of which it was reported that female students had less physical activity than male students (35).…”
Section: Discussionmentioning
confidence: 71%
“…For example, in a randomized-controlled cross-over design, a single 30-minute moderately intense aerobic treadmill session significantly (compared to a low-intensity control condition) reduced anxiety levels during a subsequent dental prophylaxis treatment in people diagnosed with dental phobia [ 59 ]. For panic disorder, promising findings were evident as well.…”
Section: Physical Activity In the Treatment Of Stress-related Disodersmentioning
confidence: 99%